The construction of the rural through social media: an imaged-based methodology to understand perceptions for the Greek countryside. (17th December 2020) - Amerani, Epistimi; Partalidou, Maria
The paper tries to discuss the social construction of rurality in the new era of mass media communication focusing, especially on perceptions of Generation Z; born and raised with the internet. The qualitative research follows an imaged-based methodology and focus group discussion. The visual analytical techniques, including content analysis and semiotic analysis showed that the positive images of rurality are dominant in the internet and social media. Through a self-coding process one third of the images define rural areas as traditional areas with intensive farming, one third landscape and the rest, social features, aging and fresh produce. As images take up an important role in our everyday life, especially through the internet and social media, there is a great potential through this methodology to understand how they shape behaviours and decisions, especially by Generation Z that will drive both consumption and labour market in the future.